Flavonoids as antiviral agents for Enterovirus A71 (EV-A71) - Lalani, S.*; Poh, Chit Laa * (MDPI, 2020)
Flavonoids are natural biomolecules that are known to be effective antivirals. These biomolecules can act at different stages of viral infection, particularly at the molecular level to inhibit viral growth. Enterovirus A71 (EV-A71), a non-enveloped RNA virus, is one of the causative agents of hand, foot and mouth disease (HFMD), which is prevalent in Asia. Despite much effort, no clinically approved antiviral treatment is available for children suffering from HFMD. Flavonoids from plants serve as a vast reservoir of therapeutically active constituents that have been explored as potential antiviral candidates against RNA and DNA viruses. Here, we reviewed flavonoids as evidence-based natural sources of antivirals against non-picornaviruses and picornaviruses.